2013
DOI: 10.1002/bit.25116
|View full text |Cite
|
Sign up to set email alerts
|

Model‐directed engineering of “difficult‐to‐express” monoclonal antibody production by Chinese hamster ovary cells

Abstract: Despite improvements in volumetric titer for monoclonal antibody (MAb) production processes using Chinese hamster ovary (CHO) cells, some "difficult-to-express" (DTE) MAbs inexplicably reach much lower process titers. These DTE MAbs require intensive cell line and process development activity, rendering them more costly or even unsuitable to manufacture. To rapidly and rationally identify an optimal strategy to improve production of DTE MAbs, we have developed an engineering design platform combining high-yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
74
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 86 publications
(86 citation statements)
references
References 44 publications
2
74
0
1
Order By: Relevance
“…In fact, PDI overexpression only increased q p for one of four monoclonal antibody (MAb) variants in a parallel experimental setup (Pybus et al, 2014). However, many cellular and experimental factors are at play when examining how an effector gene affects volumetric productivity and q p (Fig.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 3 more Smart Citations
“…In fact, PDI overexpression only increased q p for one of four monoclonal antibody (MAb) variants in a parallel experimental setup (Pybus et al, 2014). However, many cellular and experimental factors are at play when examining how an effector gene affects volumetric productivity and q p (Fig.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…However, it has been shown that both CHO-and human-derived PDI can improve q p of human MAb-related r-proteins in CHO cells (Johari et al, 2015;Mohan et al, 2007;Pybus et al, 2014) (Table 1). Moreover, XBP-1S has been shown to increase volumetric productivity and q p in…”
Section: Effector Gene Originmentioning
confidence: 99%
See 2 more Smart Citations
“…Limitations in the secretion of recombinant proteins can impact both protein quality and yield, which can have a negative impact on downstream processes. Published reports have focused on the characterization of such ‘difficult‐to‐express’ recombinant proteins and described the modification of culture conditions 6, 7, 8, 9, 10, 11, 12, 13, 14, 15 or the design of appropriate cell/protein engineering strategies to overcome restrictions in their production 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26. However, little is known regarding the mechanisms underpinning poor recombinant protein production, particularly between proteins of high sequence similarity.…”
mentioning
confidence: 99%